Happiness [videorecording (DVD)] - Solondz, Todd; Adams, Jane, 1965-; Boyle, Lara Flynn; Hoffman, Philip Seymour, 1967-2014; Gazzara, Ben, 1930-2012; Baker, Dylan (Criterion collection, 2024)
As disturbingly funny as it is audaciously empathetic, auteur of unease Todd Solondz's portrait of damaged souls reaching out for connection reveals the existential void underneath middle-class suburban "normalcy." Embodies an array of loosely connected New Jersey deviants, depressives, and misfits, among them a frustrated phone-sex pest, an all-American dad concealing his pedophilic urges, and a lonely woman with a grisly secret, all of whom want just one thing: to be loved. One of the most controversial films of the 1990s, the unflinching Happiness unnerves precisely because it dares to see humanity in those most often denied it.